2018
DOI: 10.1177/1557988318816912
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Commercially Available Mobile Phone Applications for Prostate Cancer Education

Abstract: Prostate cancer is the most commonly diagnosed non-skin cancer among all men and the second most common cause of death. To ameliorate the burden of prostate cancer, there is a critical need to identify strategies for providing men with information about prostate cancer screening and the importance of informed decision making. With mobile phones becoming more ubiquitous, many individuals are adopting their phones as sources for health information. The objective of this systematic review is to identify and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
1
21
0
1
Order By: Relevance
“…17 Five studies (22%) reported users' satisfaction of using the smartphone app. 9,13,[28][29][30] According to Pereira-Azevedo et al, 27 the mobile application has been designed to not only give patients support but also to help healthcare specialists in the process of the decision-making. The application seems to be easy to work with; hence, it is very useful in the everyday care of patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 Five studies (22%) reported users' satisfaction of using the smartphone app. 9,13,[28][29][30] According to Pereira-Azevedo et al, 27 the mobile application has been designed to not only give patients support but also to help healthcare specialists in the process of the decision-making. The application seems to be easy to work with; hence, it is very useful in the everyday care of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, one paper was excluded as it was not relevant and a further five papers were removed as they were based on unpublished or unreleased apps (not available in online stores). This left 13 papers for inclusion in our final review [12][13][14][15][16][17][18][19][20][21][22][23][24] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Analysed apps using readability studio software, over 10 readability assessments Data specifically provided on prostate cancer apps 'Cancer Conditions and Treatments' app was found to have a mean reading score of 10.2 (mean of all apps reviewed was between 9.0 and 14.6), therefore although the reading level is that of GCSE-level, it is more accessible than many of the other apps reviewed 'itsaMANTHING' app had a grade-level readability of 9.1 'Mens Health Facts And Tips' app was found to have a mean reading score of 10.6, therefore although the reading level is between GCSE and college-level, it is more accessible than many of the other apps reviewed 'Prostate Cancer' app (by developer 'Focus') had a grade-level readability of 9.5 (GCSE level) Authors stated that the prostate cancer apps (and all others included in the study) had high reading levels that preclude understanding in the average patient [19]. The study concluded that the apps included in the study were of high reading levels that were greater than that of the average patient, which might prevent patients from understanding the information they contain.…”
Section: Studies Related To 'App Readability'mentioning
confidence: 99%
See 2 more Smart Citations